RhoJ integrates attractive and repulsive cues in directional migration of endothelial cells. (29th April 2020) - Fukushima, Yoko; Nishiyama, Koichi; Kataoka, Hiroshi; Fruttiger, Marcus; Fukuhara, Shigetomo; Nishida, Kohji; Mochizuki, Naoki; Kurihara, Hiroki; Nishikawa, Shin‐Ichi; Uemura, Akiyoshi
Abstract: During angiogenesis, VEGF acts as an attractive cue for endothelial cells (ECs), while Sema3E mediates repulsive cues. Here, we show that the small GTPase RhoJ integrates these opposing signals in directional EC migration. In the GTP‐bound state, RhoJ interacts with the cytoplasmic domain of PlexinD1. Upon Sema3E stimulation, RhoJ released from PlexinD1 induces cell contraction. PlexinD1‐bound RhoJ further facilitates Sema3E‐induced PlexinD1‐VEGFR2 association, VEGFR2 transphosphorylation at Y1214, and p38 MAPK activation, leading to reverse EC migration. Upon VEGF stimulation, RhoJ is required for the formation of the holoreceptor complex comprising VEGFR2, PlexinD1, and neuropilin‐1, thereby preventing degradation of internalized VEGFR2, prolonging downstream signal transductions via PLCγ, Erk, and Akt, and promoting forward EC migration. After conversion to the GDP‐bound state, RhoJ shifts from PlexinD1 to VEGFR2, which then terminates the VEGFR2 signals. RhoJ deficiency in ECs efficiently suppressed aberrant angiogenesis in ischemic retina. These findings suggest that distinct Rho GTPases may act as context‐dependent integrators of chemotactic cues in directional cell migration and may serve as candidate therapeutic targets to manipulate cell motility in disease or tissue regeneration. Synopsis: Semaphorin 3E (Sema3E)/PlexinD1 and VEGF/VEGFR2 signalling pathways regulate endothelial cell migration in an opposite fashion. In this study, GTPase RhoJ is shown to integrate attractive and repulsive chemotactic cues by mediating interaction between VEGFR2 and PlexinD1. Sema3E releases GTP‐RhoJ from PlexinD1 to promote cell contractility. RhoJ facilitates Sema3E‐induced VEGFR2‐PlexinD1 association and p38 MAPK activation. GTP‐RhoJ sustains VEGF‐induced signalling by mediating VEFR2 interaction with PlexinD1/Neuropilin 1 complex and preventing VEGFR2 degradation. GDP‐RhoJ promotes VEGFR2 degradation, thus terminating signalling via internalized VEGFR2. RhoJ deficiency suppresses aberrant angiogenesis in ischemic retina. Abstract : RhoJ GTPase regulates angiogenesis and endothelial cell migration in a context‐dependent fashion by mediating ligand‐dependent interaction between VEGFR2 and PlexinD1.